(untitled) (Sciences & Technology. A, exactes sciences, 2007)
Pulsed ruby, pulsed and scanned YAG, and CO2 lasers have been used to crystallize thin C.V.D. deposited amorphous undoped silicon layers. Substrates are singlr crystal Si (100) or amorphous SiO2. The annealed layers have been investigated by RBS and TEM, using both plan viewed and cross - sectional samples. The roles played by the nature of the substrate and by the large amount of nitrogen in the deposited layers are studied. The major observations made during these investigations are qualitatively discussed